Sulfur utilization by rice and Crotalaria juncea from sulfate - 34S applied to the soil (Scientia Agricola, 2002)
In tropical soils with intensive agriculture an increasing sulfur deficiency has been verified in several crops. The low available S in these soils is caused by the continuous use of concentrated NPK fertilizers. The objective of this work was to evaluate the utilization by rice (Oriza sativa L.) and crotalaria juncea (Crotalaria juncea L.) of sulfur applied to the soil, under greenhouse conditions. Pots with 3 kg of an Argisol (Paleudalf) were used to test the isotopic technique with the stable isotope 34S, adding a solution of sodium sulfate labeled with 34S (14.30 ± 0.05 atom % of 34S) to the soil (70 mg SO4-S per kg-1 of soil) 18 days after sowing both species. The shoots of the crotalaria and rice were harvested, respectively on the 72nd and 122nd days after S fertilization. The concentration and the amount of sulfur in the crotalaria were higher than in rice, due to the higher legume requirement for this nutrient. The sulfur requirement and the short time interval between fertilization and harvest of the crotalaria resulted in a small amount of native SO4-S mineralized in the soil and a small quantity of 34SO4 immobilized by soil microorganisms. Thus, the percentage of sulfur in the crotalaria derived from the fertilizer (Sdff) was higher than in the rice (%Sdff crotalaria = 91.3 ± 3.5%; %Sdff rice = 66.3 ± 0.8%). The expressive values of %Sdff indicate a low rate of mineralization of SO4-S probably as a consequence of the low available sulfur content in the soil.